Location of Zeros for the Weak Solution to a $p$-Ginzburg-Landau Problem (Communications in Mathematical Research, 2019)
This paper is concerned with the asymptotic behavior of the solution $u_ε$of a $p$-Ginzburg-Landau system with the radial initial-boundary data. The authorproves that the zeros of $u_ε$ in the parabolic domain $B_1(0)× (0,\,T]$ locate near theaxial line $\{0\}×(0,\,T]$. In particular, all the zeros converge to this axial line when theparameter $ε$ goes to zero.